DMT MIMO IC rate maximization in DSL with per-transceiver power constraints - Moraes, Rodrigo B.; Tsiaflakis, Paschalis; Maes, Jochen; Moonen, Marc (Signal processing, 2014)
This paper deals with the discrete multitone multiple input, multiple output interference channel (DMT MIMO IC) in DSL networks. The scenario consists of a number of users, each with a given number of transceivers, that share the same channel in multiple tones. Our goal is to maximize the weighted rate sum of the users subject to power constraints. A recent paper has treated this problem with per-user power constraints. In this paper we focus on per-transceiver power constraints. We propose two different algorithms. First, we straightforwardly adapt the previously proposed DMT-WMMSE algorithm. Second, we adapt the WMMSE-GDSB, in which we separate the problem in signal and spectrum coordination parts. For the spectrum coordination part, we show that the problem can be solved more efficiently with a change of variables: we use a coordinate system consisting of a radius and a direction vector with ℓ1 norm equal to 1. This can be interpreted as spherical coordinates in taxicab geometry. It is observed that for the radial dimension the problem can be made concave after approximations and it is thus easy to solve. The remaining dimensions are solved with a sequence of line searches. Simulation results show that the WMMSE-GDSB converges faster. •We focus on the DMT MIMO IC problem with per-transceiver power constraints.•First, we develop a version of the previously proposed DMT-WMMSE.•Second, we develop an algorithm with separated signal and spectrum coordination parts.•For the spectrum part, we use spherical coordinates in taxicab geometry.•Both algorithms perform well, but the second one is observed to be faster.